Teaching social robots: the effect of robot mistakes on children's learning-through-teaching - Bowman-Smith, Celina K.; Aitken, Charlotte; Mahenthiran, Thuvaraka; Law, Edith; Nilsen, Elizabeth S. (Frontiers in Developmental Psychology, 2025)
Social robots are increasingly being designed for use in educational contexts, including in the role of a tutee. However, little is known about how robot behavior affects children's learning-through-teaching. We examined whether the frequency and type of robot mistakes affected children's teaching behaviors (basic and advanced), and subsequent learning, when teaching a social robot. Eight to 11-year-olds (N = 114) taught a novel classification scheme to a humanoid robot. Children taught a robot that either made no mistakes, typical mistakes (errors on untaught material; accuracy on previously taught material), or atypical mistakes (errors on previously taught material; accuracy on untaught material). Following teaching, children's knowledge of the classification scheme was assessed, and they evaluated their own teaching and both their own and the robot's learning. Children generated more teaching strategies when working with one of the robots that made mistakes. While children indicated that the robot that made typical mistakes learned better than the one that made atypical mistakes, children themselves demonstrated the most learning gains if they taught the robot that made atypical mistakes. Children who demonstrated more teaching behaviors showed better learning, but teaching behaviors did not account for the learning advantage of working with the atypical mistake robot.